PATTERN OF DYSLIPIDAEMIA AND ITS ASSOCIATION WITH HYPOVITAMINOSIS D IN TYPE 2 DIABETES MELLITUS - Bashir, Farhat; Khan, Zia Ullah; Seetlani, Naresh Kumar; Sheikh, Zaman (Journal of Ayub Medical College Abbottabad, 2017)
Background: Macrovascular atherosclerosis is an important long-term complication of type 2 diabetes mellitus. Concurrent dyslipidaemia acts as an additional risk factor for these complications. Hypovitaminosis D has been associated with adverse cardiovascular events. These modifiable risk factors of cardiovascular disease are inter-related. In the presence of an increasing incidence of type 2 diabetes mellitus and its associated metabolic abnormalities and widespread vitamin D deficiency in Pakistan, this association needs to be investigated. The purpose of our study was to determine the pattern of dyslipidaemia and its association with low vitamin D levels in South Asian diabetics. Methods: The study was designed as a quantitative cross-sectional study. It was conducted at the Department of Medicine, Sir Syed College of Medical Sciences and Hospital, Karachi from January to June 2014. A total of 168 adult consecutive patients with type 2 diabetes mellitus of both the genders were included. Data was collected and analysed using SPSS-20.0. The association of dyslipidaemia with vitamin D status was computed through Chi-square test. Results: We found that dyslipidaemia is highly prevalent in patients with type 2 diabetes mellitus in Pakistan. High total cholesterol, LDL cholesterol and triglycerides show significant association with vitamin D deficiency. Conclusion: In order to decrease the development of diabetic complications aggressive management of hyperglycaemia and dyslipidaemia is required. Vitamin D supplementation may play a dual role in these situations. Keywords: Dyslipidaemia; Type 2 diabetes mellitus; Vitamin D; Hypovitaminosis D